Integrating BAZNAS and Sharia Microfinance for Inclusive Economic Empowerment in Indonesia - Sari Damayanti; Nurrohman; Ahmad Hasan Ridwan; Sri Dewi Anggadini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The Sharia economy in Indonesia has great potential to improve public welfare but faces challenges such as limited capital access, low Islamic finance literacy, and dependence on illegal loans. Micro Sharia financing has proven capable of empowering MSMEs, improving community livelihoods, and reducing reliance on exploitative credit, thus strengthening the national economy. BAZNAS Microfinance, through productive zakat integration, provides interest-free capital, business support, and capacity building for mustahik, enhancing economic independence. This study examines an integrated model between Sharia Microfinance (LKMS/BMT) and BAZNAS Microfinance as a strategic instrument for economic empowerment within the maqāṣid al-sharīah framework. Using a qualitative-descriptive method with conceptual and normative-synthetic analysis, it combines Islamic economics theory, maqāṣid al-sharīah, and socio-financial practices of BAZNAS and LKMS. Findings show that synergy between Islamic social funds and commercial microfinancing creates a sustainable Islamic economic ecosystem. Through social incubation, productive financing, and economic circulation, the model reduces dependence on exploitative loans while expanding inclusive access to halal capital and supporting long-term community resilience. Theoretical foundations, including maqāṣid al-sharīah, ontology, axiology, and charity theory, strengthen its sustainability and relevance for equitable and inclusive economic development.